Development of Jumanji Board Game Media on Ecosystem Material in Islamic Elementary School - Maghfirotul Firmaning Lestari; Muhammad Suwignyo Prayogo (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah)
The article aims to develop a Jumanji board game media in class V Madrasah Ibtidaiyah At-Taqwa Bondowoso. Learning media has a somewhat important role in learning because it can make it easier for teachers to convey learning objectives to their students. From this, of course, it is necessary to develop learning media tailored to the needs of schools and the characteristics of students. The research results found that the enthusiasm and motivation to learn were still lacking, and the understanding of the material needed improvement. With the Jumanji board game, the media can overcome the obstacles that have been mentioned. Researchers use the R&D method using the ADDIE model, namely analysis, design, development, implementation, and evaluation. The result of this study is that researchers developed a learning media called the Jumanji Board. This media is a learning medium that can invite students to play while learning. The Jumanji board game media has colourful cards, game lines, pawns, dice, and sand time. This, of course, can attract students' motivation because, based on the study results, it was found that the enthusiasm and motivation to learn were still lacking, and the understanding of the material still needed to be improved. With the Jumanji board game, the media can overcome the obstacles that have been mentioned. The acquisition of media validation from expert validators obtained an average value of 90%. The results of this validation indicate that the Jumanji board game media has met the valid category or is very suitable for use.